Sodium-ion battery diaphragm

By adopting a multi-layer structure in the sodium ion battery separator, combining nano-silicon oxide, polyvinylidene fluoride/polypropylene composite film layer and other functional layers, and setting reinforcement ribs, the problems of poor wettability, low mechanical strength and poor thermal stability of the separator are solved, and a high-performance sodium ion battery separator is achieved.

CN222802038UActive Publication Date: 2025-04-25XI AN JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420802286.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-17
Publication Date
2025-04-25
Estimated Expiration
2034-04-17

AI Technical Summary

Technical Problem

The existing sodium ion battery separators have problems such as poor wetting, low mechanical strength and poor thermal stability, which affect the safety and circulation performance of the battery.

Method used

Carboxymethylcellulose/carboxyethylcellulose porous separator layer is used as the basis, and nano-silicon oxide layer, polyvinylidene fluoride/polypropylene composite film layer, polyethylene microsphere layer, polytetrafluoroethylene layer and polydopamine layer are combined, and reinforcement ribs are provided between each layer to improve the mechanical properties and ion conduction ability of the separator.

Benefits of technology

The high wettability, mechanical strength and thermal stability of the sodium ion battery separator are achieved, the growth of sodium dendrites is inhibited, and the safety and circulation performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222802038U_ABST
    Figure CN222802038U_ABST
Patent Text Reader

Abstract

The utility model provides a sodium ion battery diaphragm which comprises a carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer, and a nano silicon oxide layer and a polyvinylidene fluoride / polypropylene composite film layer are sequentially arranged on one side of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer. According to the utility model, the composite film formed by the polyvinylidene fluoride and the polypropylene film has better electrolyte affinity and mechanical strength, including tensile strength and puncture resistance, when the composite film is used as the upper layer film; the nano silicon oxide layer has the characteristics of good thermal stability and high mechanical property, so that the high temperature resistance and mechanical property of the diaphragm can be improved, and dendritic crystal penetration can be blocked; the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer has high porosity and uniform pore distribution, provides high-speed ion conduction capability and electrolyte retention rate for the diaphragm, regulates sodium ion flux, realizes uniform sodium deposition, and inhibits the growth of sodium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of battery diaphragms, in particular to a sodium ion battery diaphragm. Background Art

[0002] The electrochemical performance of sodium-ion batteries is closely related to the cathode, anode, electrolyte and separator. In the early stages of battery development, most research efforts focused on electrode materials and electrolytes, with less attention paid to separators. However, when considering large-scale production of batteries, separators have to be considered. The separator is a key part inside a sodium-ion battery that isolates the positive and negative electrodes and stores electrolytes to freely transmit sodium ions.

[0003] Glass fiber (GF) is widely used in sodium-ion batteries due to its high porosity, wettability and excellent thermal stability. However, it still has the problems of large thickness and poor mechanical properties. Its excessive porosity requires a large amount of electrolyte to fill it, and the safety problem caused by the easy leakage of electrolyte is also very prominent, so it is only used in laboratory research. The large pores and uneven pore structure of glass fiber easily deposit sodium metal at the negative electrode and induce the growth of dendrites, resulting in short circuit between the positive and negative electrodes and capacity decay.

[0004] Commercial olefin separators, especially PP-PE-PP triple membranes, are widely used in sodium-ion batteries. They have good electrochemical stability and high mechanical strength, but their stability at high temperatures is very poor, and their electrolyte wettability is poor and their pore size is unstable.

[0005] Cellulose is an abundant and renewable natural polymer material, which is widely used in the field of energy storage due to its excellent structural properties and low price. It has the characteristics of easy processing, high heat resistance, good chemical stability, excellent wettability, etc., and is considered by scholars to be a material that can replace polyolefin raw materials to prepare battery separators. Cellulose films usually have porosity, ionic conductivity, mechanical stability and chemical stability, so high-performance separators can be made in lithium-ion batteries. Similarly, cellulose films have attracted much attention in SIB systems. However, the large pore size and low mechanical strength of cellulose films hinder the safety and cycle performance of batteries. Utility Model Content

[0006] The utility model aims to provide a sodium ion battery separator to solve the problems of poor wettability, low mechanical strength and poor thermal stability of the separator in the above-mentioned prior art.

[0007] The utility model is realized by the following technical solutions:

[0008] A sodium ion battery separator comprises a carboxymethyl cellulose / carboxyethyl cellulose porous separator layer, wherein a nano silicon oxide layer and a polyvinylidene fluoride / polypropylene composite membrane layer are sequentially arranged on one side of the carboxymethyl cellulose / carboxyethyl cellulose porous separator layer.

[0009] Preferably, a polyethylene microsphere layer is disposed on the other side of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer.

[0010] Furthermore, a polytetrafluoroethylene layer is provided on the polyethylene microsphere layer.

[0011] Furthermore, a polydopamine layer is provided on the polytetrafluoroethylene layer.

[0012] Furthermore, the thickness of the polyethylene microsphere layer is 0.1-2 μm, the thickness of the polytetrafluoroethylene layer is 0.5-5 μm, and the thickness of the polydopamine layer is 1-5 μm.

[0013] Furthermore, reinforcing ribs are arranged on both sides of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer, the reinforcing ribs on one side are arranged in the nano silicon oxide layer, and the reinforcing ribs on the other side penetrate the polyethylene microsphere layer and the polytetrafluoroethylene layer.

[0014] Furthermore, the reinforcing rib is V-shaped.

[0015] Furthermore, the opening directions of two adjacent reinforcing ribs located on the same side of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer are opposite.

[0016] Furthermore, the reinforcing ribs are made of polymer fiber.

[0017] Preferably, the thickness of the nano silicon oxide layer is 0.2-6 μm, the thickness of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer is 5-35 μm, and the thickness of the polyvinylidene fluoride / polypropylene composite membrane layer is 0.5-3 μm.

[0018] Compared with the prior art, the utility model has the following beneficial effects:

[0019] In the utility model, the sodium ion battery separator is composed of a polyvinylidene fluoride / polypropylene composite film layer, a nano silicon oxide layer, and a carboxymethyl cellulose / carboxyethyl cellulose porous separator layer from top to bottom. The composite membrane composed of polyvinylidene fluoride and polypropylene film has better electrolyte affinity and mechanical strength when used as an upper membrane, including tensile strength and puncture resistance; the nano silicon oxide layer has the characteristics of good thermal stability and high mechanical properties, which can improve the high temperature resistance and mechanical properties of the separator and prevent dendrites from penetrating; the carboxymethyl cellulose / carboxyethyl cellulose porous separator layer has a high porosity and uniform pore distribution, which provides the separator with high-speed ion conduction ability and electrolyte retention rate, regulates the sodium ion flux, and realizes uniform sodium deposition to inhibit the growth of sodium dendrites. Therefore, the sodium ion battery separator of the utility model has the advantages of inhibiting the growth of sodium dendrites, good wettability, high mechanical strength and high thermal stability.

[0020] Furthermore, the polyethylene microsphere layer is melted and blocks the micropores of the diaphragm when thermal runaway occurs in the battery, thereby preventing the thermal runaway reaction from proceeding.

[0021] Furthermore, the polytetrafluoroethylene layer does not decompose at 250°C while maintaining high porosity and liquid electrolyte absorption rate, has high thermal stability, and improves the heat resistance of the overall diaphragm.

[0022] Furthermore, the high electrolyte wettability of the polydopamine layer enhances the sodium ion transfer capacity, further inhibits the growth of sodium dendrites at the molecular level, and guides the uniform deposition of sodium.

[0023] Furthermore, in the utility model, a plurality of reinforcing ribs are provided between the polyvinylidene fluoride / polypropylene composite film layer and the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer, and between the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer and the polydopamine layer. The reinforcing ribs improve the connectivity between the layers and enhance the strength of the overall diaphragm, thereby avoiding the effects of deformation and dislocation of the battery diaphragm during bending or winding on the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the utility model or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the utility model. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 It is a schematic diagram of the overall structure of the utility model.

[0026] In the figure: 1. Carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer; 2. Nano-silicon oxide layer; 3. Polyvinylidene fluoride / polypropylene composite membrane layer; 4. Polyethylene microsphere layer; 5. Polytetrafluoroethylene layer; 6. Polydopamine layer; 7. Reinforcing ribs. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the utility model to clearly and completely describe the technical solutions in the embodiments of the utility model. Obviously, the described embodiments are only part of the embodiments of the utility model, not all of the embodiments. Based on the embodiments of the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.

[0028] In the description of the present application, it should be noted that the terms used herein are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. For ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, rather than as a limitation. Therefore, other examples of the exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.

[0029] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described here, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.

[0030] It should be noted that, in the description of the present application, the orientation or positional relationship indicated by terms such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description. Unless otherwise stated, these orientation words do not indicate or imply that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application; the orientation words "inside and outside" refer to the inside and outside relative to the contour of each component itself.

[0031] It should be noted that, in the present application, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0032] See also Figure 1 , the utility model provides a technical solution:

[0033] A sodium ion battery separator comprises a carboxymethyl cellulose / carboxyethyl cellulose porous separator layer 1, on one side of which a nano silicon oxide layer 2 and a polyvinylidene fluoride / polypropylene composite membrane layer 3 are sequentially arranged.

[0034] As an example of the present invention, a polyethylene microsphere layer 4 is further provided on the other side of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer 1. Preferably, a polytetrafluoroethylene layer 5 may be provided on the polyethylene microsphere layer 4, and more preferably, a polydopamine layer 6 may be further provided on the polytetrafluoroethylene layer 5.

[0035] As an example of the present invention, reinforcing ribs 7 are provided on both sides of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer 1. The reinforcing ribs 7 on one side are arranged in the nano silicon oxide layer 2, and the reinforcing ribs 7 on the other side penetrate the polyethylene microsphere layer 4 and the polytetrafluoroethylene layer 5.

[0036] As an example of the present invention, the reinforcing rib 7 is V-shaped, and the opening directions of two adjacent reinforcing ribs 7 on the same side of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer 1 are opposite.

[0037] As an example of the present invention, the nano-silicon oxide layer 2 is coated on the surface of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer 1 by in-situ growth, chemical vapor deposition, and scraping. Its thickness is 0.2-6 μm, the porosity is 40%-60%, and the size of the nano-silicon oxide is 2-50 nm.

[0038] As an example of the present invention, the carboxymethyl cellulose / carboxyethyl cellulose porous membrane layer 1 has a thickness of 5 to 35 μm and a porosity of 20% to 55%.

[0039] As an example of the present utility model, the thickness of the polyvinylidene fluoride / polypropylene composite film layer 3 is 0.5 to 3 μm, and the porosity is 35% to 60%.

[0040] As an example of the present invention, the polyethylene microsphere layer 4 has a thickness of 0.1-2 μm, a porosity of 30%-60%, and a size of 0.5-1 μm.

[0041] As an example of the present invention, the thickness of the polytetrafluoroethylene layer 5 is 0.5-5 μm, and the porosity is 20%-60%.

[0042] As an example of the present invention, the thickness of the polydopamine layer 6 is 1-5 μm, and the porosity is 20%-55%.

[0043] As an example of the present invention, the V-shaped reinforcing rib material is a polymer fiber, such as silicon carbide fiber, nylon fiber, and aramid (such as aramid 1313 fiber).

[0044] The working principle of the utility model is as follows: a sodium ion battery diaphragm is prepared by compounding a polyvinylidene fluoride / polypropylene composite film layer 3, a nano silicon oxide layer 2, a carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer 1, a polyethylene microsphere layer 4, a polytetrafluoroethylene layer 5, a polydopamine layer 6 and a V-shaped reinforcing rib. The composite membrane composed of polyvinylidene fluoride and polypropylene has better electrolyte affinity and mechanical strength, including tensile strength and puncture resistance, when used as the upper membrane; the nano-silicon oxide layer has the characteristics of good thermal stability and high mechanical properties, which can improve the high temperature resistance and mechanical properties of the diaphragm and prevent dendrite penetration; the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer has high porosity and uniform pore distribution, which provides the diaphragm with high-speed ion conductivity and electrolyte retention rate, regulates the sodium ion flux, and achieves uniform sodium deposition to inhibit the growth of sodium dendrites; the polyethylene microspheres melt and block the micropores of the diaphragm when the battery has thermal runaway, thereby preventing the thermal runaway reaction from proceeding; while maintaining high porosity and liquid electrolyte absorption rate, the polytetrafluoroethylene layer will not decompose at 250°C, has high thermal stability, and improves the heat resistance of the overall diaphragm; and the high electrolyte wettability of the polydopamine layer enhances the sodium ion transfer ability, further inhibits the growth of sodium dendrites at the molecular level, and guides the uniform deposition of sodium. The reinforcing ribs improve the connectivity between the layers and increase the strength of the overall separator, thereby preventing deformation and dislocation of the battery separator during bending or winding from affecting battery performance.

[0045] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A sodium ion battery separator, characterized in that: The invention comprises a carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer (1), wherein a nano silicon oxide layer (2) and a polyvinylidene fluoride / polypropylene composite membrane layer (3) are sequentially arranged on one side of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer (1).

2. The sodium ion battery separator according to claim 1, characterized in that A polyethylene microsphere layer (4) is provided on the other side of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer (1).

3. The sodium ion battery separator according to claim 2, characterized in that: A polytetrafluoroethylene layer (5) is arranged on the polyethylene microsphere layer (4).

4. The sodium ion battery separator according to claim 3, characterized in that A polydopamine layer (6) is arranged on the polytetrafluoroethylene layer (5).

5. The sodium ion battery separator according to claim 4, characterized in that: The thickness of the polyethylene microsphere layer (4) is 0.1 to 2 μm, the thickness of the polytetrafluoroethylene layer (5) is 0.5 to 5 μm, and the thickness of the polydopamine layer (6) is 1 to 5 μm.

6. The sodium ion battery separator according to claim 3, characterized in that: Reinforcing ribs (7) are provided on both sides of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer (1), the reinforcing ribs (7) on one side are arranged in the nano silicon oxide layer (2), and the reinforcing ribs (7) on the other side penetrate the polyethylene microsphere layer (4) and the polytetrafluoroethylene layer (5).

7. The sodium ion battery separator according to claim 6, characterized in that: The reinforcing rib (7) is V-shaped.

8. The sodium ion battery separator according to claim 7, characterized in that: The opening directions of two adjacent reinforcing ribs (7) located on the same side of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer (1) are opposite.

9. The sodium ion battery separator according to claim 8, characterized in that: The material of the reinforcing rib (7) is polymer fiber.

10. The sodium ion battery separator according to claim 1, characterized in that: The thickness of the nano silicon oxide layer (2) is 0.2 to 6 μm, the thickness of the carboxymethyl cellulose / carboxyethyl cellulose porous diaphragm layer (1) is 5 to 35 μm, and the thickness of the polyvinylidene fluoride / polypropylene composite membrane layer (3) is 0.5 to 3 μm.